Chapter Natural Gas Catalytic Partial Oxidation: A Way to Syngas and Bulk Chemicals Production - Guarinoni, Alessandra; Antonetti, Elena; Lainati, Andrea; Cucchiella, Barbara; Salladini, Annarita; Iaquaniello, Gaetano; Basini, Luca; Palo, Emma (InTechOpen, 2021)
Computer modelling & simulation